Greece 2021: Official and lay understandings of national identity - Stratoudaki, Hara (Social Cohesion and Development, 2024)
Jubilees and national days are privileged opportunities for (re)negotiating national identity and its markers. They offer both to the states and groups of citizens or minorities within states, the opportunity to assure or challenge accepted forms of identity. The Bicentennial of the Greek Revolution, which is the founding moment of modern Greek state, was no exception to this. In this paper we present a synopsis of the public discourses about the meaning of the Bicentennial and the role of the Committee 2021 which was assigned to oversee the preparations and select projects to include in the year-round celebration. We then contrast those discourses to the ones found in the Facebook posts reacting to the proposal of the emblem of the Bicentennial. We find that contrary to conventional wisdom, it is the state and its institutions that opted for a new identity narrative, while the ordinary citizens who decided to express their opinion were resisting such a novelt